Programação aplicada ao desenvolvimento do projecto - Henrique Manuel Robalo Martinho (2022)
The evolution of digital systems during the XX and XXI centuries changed the work paradigm of the architects and dynamized project development by creating new possibilities. This work initiates by analysing the influence of digital technologies on the evolution of the project development processes and how these new tools are currently used to develop architecture projects. Afterwards there will be analysed 5 digital work methodologies, CAD, BIM, AAD, AABIM and computer programming/scripting. These 5 working methodologies will be described with the intention of understanding how can each one of these contribute to the project development, identifying the possibilities and limits of each one of them. Following that, there will be studied 5 case studies that demonstrate practical applications of each one of these methodologies and how their characteristics optimised and improved the development process of various projects. At last, this work will bring into focus computer programming/scripting to better understand and demonstrate how a greater computer control through High- Level programming languages (like Python for example) can improve the working possibilities of the project developer. In this module, there will be presented some examples (that were created and developed during this work) that demonstrate some practical coding/scripting applications on the architects work and how programming knowledge can be used to overcome some limits found on the other digital work methodologies.